Microstrip line Antenna Fabrication Material - Singh, Vimlesh; Bansal, Priyanka; K.Singhal, P (International Journal of Engineering and Technology, 2018)
This paper presents an extensive survey of electromagnetic materials used for antenna fabrication, which find application in Civilian life as well as defense life. When a densely packed microwave integrated circuit is designed, it requires protection from higher power transient because of specific polarization and frequency response. To meet specification of such kind of microwave circuits it is desired to exploit properties of fabricating materials, which are not found in nature but can be prepared with specific proportion of chemical element combination. This study provides in-depth responses of materials toward electromagnetic wave's characteristics such as dielectric, flexible electronics, electrical and thermal properties, which have vast potential in communication engineering.